The RPA of renormalized fermions - Dussel, Guillermo Gaspar; Perazzo,Roberto Pedro J.; Spina, María Elena (North Holland Publishin Co., 1981)
Fil: Dussel, Guillermo Gaspar Comisión Nacional de Energía Atómica; Argentina